Promoting Drp1-mediated mitochondrial fission in midlife prolongs healthy lifespan of Drosophila melanogaster - Anil Rana (Nature Portfolio, 2017)
Mitochondrial fission and fusion are important mechanisms to maintain mitochondrial function. Here, the authors report that middle-aged flies have more elongated, or ‘hyper-fused’ mitochondria, and show that induction of mitochondrial fission in midlife, but not in early life, extends the health and life of flies.